Analysis of cryptocurrency as collateral from the perspective of Indonesian positive law and Islamic law: A comparison - Jamie Armadi Jaya; Henry Anderson Parapat; Ahmad Mubarak; Etra Arbas (Privietlab, 2025)
Current technology has significantly impacted several sectors, including the financial sector. Cryptocurrency is one of the financial technology phenomena currently being widely discussed. Cryptocurrency is a digital currency that holds value and can become a promising asset for its holders. This study focuses on cryptocurrency as collateral from Indonesian and Islamic legal perspectives. This research method emphasizes a rules-based approach, namely, through laws and other legal sources. The findings indicate that Indonesian legal support for cryptocurrency as collateral is valid because it is a movable asset. However, from an Islamic legal perspective, collateral is known as al-Rahn. The use of cryptocurrency as an object in an al-rahn contract is considered invalid. This is because, from an Islamic perspective, cryptocurrency does not fulfill Shariah principles. This asset contains elements of gharar (uncertainty), dharar (potential harm), and maysir or qimar (elements of speculation or gambling), so it is considered unfit to be used as goods (sil'ah) in transactions that comply with sharia.